Transporters as Targets for Drugs - Napier, Susan; Bingham, Matilda (Topics in Medicinal Chemistry, 2009)
M. Bingham • S. Napier: Overview: Transporters as Targets for Drug Discovery I. Sylte • A.W. Ravna • G. Sager • S.G. Dahl: Membrane Transporters: Structure, Function and Targets for Drug Design G.A. Whitlock • M.D. Andrews • A.D. Brown • P.V Fish • A. Stobie • F. Wakehut: Design of Monoamine Reuptake Inhibitors - SSRIs, SNRIs and NRIs A. Hauck Newman • J.L. Katz: Atypical Dopamine Uptake Inhibitors that Provide Clues About Cocaine's Mechanism at the Dopamine Transporter Z. Chen • J. Yang • P. Skolnick: The Design, Synthesis and Structure-Activity Relationship of Mixed Serotonin, Norepinephrine and Dopamine Uptake Inhibitors G. Antoni • J. Sörensen • H. Hall: Molecular Imaging of Transporters with Positron Emission Tomography R. Bridges • S.A. Patel: Pharmacology of Glutamate Transport in the CNS: Substrates and Inhibitors of Excitatory Amino Acid Transporters (EAATs) and the Glutamate/Cystine Exchanger System xc R. Gilfillan • J. Kerr G. • Walker • G. Wishart: Glycine Transporters and Their Inhibitors.